2016
DOI: 10.1186/s40824-016-0076-0
|View full text |Cite
|
Sign up to set email alerts
|

A branched TAT cell-penetrating peptide as a novel delivery carrier for the efficient gene transfection

Abstract: BackgroundCell penetrating peptides (CPPs) as one class of non-viral vectors, have been widely explored as a delivery tool due to their cell-penetrating capability with low cytotoxicity. However, CPPs have reported to have low gene transfection efficiency mainly due to the fact that DNA is larger than other biomolecules. On the other hand, the conventional linear CPPs are unstable for constructing the DNA complexes with it. Thus, here we designed a branched CPP using disulfide bridges based on the linear TAT p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Also, the modified CPPs with cysteine could improve their properties. For example, the branched Tat (BTat), a modified type of Tat (Cys-Tat-Cys-Tat-Cys) with disulfide bonds formed the complexes with plasmid DNA harboring GFP gene and showed higher transfection efficiency (~40-fold) than the Tat/ DNA complexes [218]. Saleh et al demonstrated that covalent linkage of membrane active peptide LK15 to Tat peptide improved its gene transfer likely due to the higher uptake of DNA [219].…”
Section: Nucleic Acid Deliverymentioning
confidence: 99%
“…Also, the modified CPPs with cysteine could improve their properties. For example, the branched Tat (BTat), a modified type of Tat (Cys-Tat-Cys-Tat-Cys) with disulfide bonds formed the complexes with plasmid DNA harboring GFP gene and showed higher transfection efficiency (~40-fold) than the Tat/ DNA complexes [218]. Saleh et al demonstrated that covalent linkage of membrane active peptide LK15 to Tat peptide improved its gene transfer likely due to the higher uptake of DNA [219].…”
Section: Nucleic Acid Deliverymentioning
confidence: 99%
“…20 In more recent work, branched polycationic peptides have even been successfully employed as gene transfection tools as well. 21,22…”
Section: Introductionmentioning
confidence: 99%
“…However, it is rather high molecular size brings toxicity issues for the host cells (Nam et al ., 2015) or decreases the cell metabolic activity (Fischer et al ., 1999; Godbey et al ., 2001; Florea et al ., 2002). Although a CPP alone is unable to properly condense DNA plasmid (Jeong et al ., 2016), the combination of CPPs and PEI significantly improves the transfection efficiency. Moreover, some CPPs namely octaarginine can also inhibit the intracellular proteolytic systems like the proteasome (Kloß et al ., 2009) but it is unknown whether they can permanently inhibit cellular function.…”
Section: Discussionmentioning
confidence: 97%